WORLD EXPERIENCE OF SOCIAL RESPONSIBILITY OF BANKS - Bimuratova Aigerim; Tokareva Elena; Makhatova Adelina; Cherep Alla (Scientific Journal of Pedagogy and Economics, 2020)
The commercial activities of banks directly affect the society in which they operate, and future business successes are closely linked to key social values. Considering the specifics of the activities of commercial banks, trust is becoming one of the most important conditions for a normally functioning banking services market, and the level of profits is increasingly determined not by the technology of the provision of services, but by the correct positioning of banks in the social environment based on social responsibility and reputation. The level of socially responsible behavior of banks has a direct impact not only on the sustainable development of society, but also on the stability of the banks themselves. The problem of corporate social responsibility is increasingly reflected in the media and scientific works of prominent scientists. It must be understood that the social responsibility of business is much wider than is commonly believed.